2014
DOI: 10.1080/19393210.2013.861518
|View full text |Cite
|
Sign up to set email alerts
|

Patulin in apple juices from the Romanian market

Abstract: The aim of this study was to determine patulin levels in apple-based juices from the Romanian market and to establish a health risk assessment. For this purpose, 50 samples of apple-based juices have been purchased from the Romanian market. Aliquots were extracted by liquid-liquid extraction using ethyl acetate, analysed and quantified using a high-performance liquid chromatography (HPLC) method. The patulin level in the apple juices from Romania ranged between <0.7 μg/l and 101.9 μg/l. In 6% of the 50 samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 28 publications
3
6
1
Order By: Relevance
“…Results of this study showed only 4 out of 161 samples that exceeded the maximum limit (50 µg/kg) as set for PAT in fruit juice by European legislation (EC 2006). Although different extraction and detection techniques were used, similar incidences in terms of both positive samples and detected levels of PAT in apple products have been reported from Japan (Ito et al 2004), Italy (Spadaro et al 2007), Portugal (Barreira et al 2010), China (Yuan et al 2010), Spain (Marín et al 2011), Tunisia (Zaied et al 2013) and Romania (Oroian et al 2014) and lower than those reported by Gökmen and Acar (1998) Arabia. Our results, however, are higher than those reported by Iha and Sabino (2008) from Brazil.…”
Section: Resultssupporting
confidence: 64%
“…Results of this study showed only 4 out of 161 samples that exceeded the maximum limit (50 µg/kg) as set for PAT in fruit juice by European legislation (EC 2006). Although different extraction and detection techniques were used, similar incidences in terms of both positive samples and detected levels of PAT in apple products have been reported from Japan (Ito et al 2004), Italy (Spadaro et al 2007), Portugal (Barreira et al 2010), China (Yuan et al 2010), Spain (Marín et al 2011), Tunisia (Zaied et al 2013) and Romania (Oroian et al 2014) and lower than those reported by Gökmen and Acar (1998) Arabia. Our results, however, are higher than those reported by Iha and Sabino (2008) from Brazil.…”
Section: Resultssupporting
confidence: 64%
“…The contamination of apple juices to PAT has been studied in various countries such as Spain (0.7–118 µg L −1 ), Iran (50–285 µg L −1 ), the Netherlands (25–200 µg L −1 ), Italy (2–56 µg L −1 ), Saudi Arabia (5–152.5 µg L −1 ), Portugal (1.2–42 µg L −1 ) and Romania (0.7–101.9 µg L −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical structure of patulin. Saudi Arabia 10 (5-152.5 μg L −1 ), Portugal 11 (1.2-42 μg L −1 ) and Romania 12 (0.7-101.9 μg L −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of reports show frequent occurrence of patulin, although at different level, in apples and various apple-based food commodities from over the World, i.e., Qatar (Hammami et al 2017), Portugal (Barreira et al 2010), Spain (Murillo-Arbizu et al 2009Marsol-Vall et al 2014), Italy (Ritieni 2003;Piemontese et al 2005), Czech Republic (Vaclavikova et al 2015), Romania (Catana et al 2011;Oroian et al 2014), Tunisia (Zaied et al 2013;Zouaoui et al 2015), Brazil (Sargenti and Almeida 2010), Argentina (Funes and Resnik 2009), United States (Harris et al 2009), Iran (Jalali et al 2010;Forouzan and Madadlou 2014), Pakistan (Iqbal et al 2018), South Korea (Cho et al 2010), and Northeast China (Yuan et al 2010). According to published data, patulin concentration in the infected apples could reach 8.8-120.4 mg kg −1 (Piemontese et al 2005;Wu et al 2008;Gaspar and Lucena 2009) (Celli et al 2009).…”
Section: Patulin Occurrence In Fruit Commoditiesmentioning
confidence: 99%